Rethinking the Research Agenda - Perraton, Hilary (International Review of Research in Open and Distributed Learning, 2000)
Research is seen as something grounded in theory that can lead to improved practice. Without a theoretical basis it is unlikely to go beyond data gathering. The theoretical insights leading to good research are more likely to come from educational and social theories generally than from an attempt to develop a theory of open and distance learning. An examination of existing research shows that it is often atheoretical and predominantly descriptive. Research on the context of open and distance learning, considering its purposes, outcomes, and relevance to major educational problems, has been relatively neglected as contrasted with research on its application. Significant research issues today include: problems posed by globalisation, including issues of governance and consumer protection; ways of maximising public benefit from new communication technologies; the development of strategies for AIDS education; and the continuing need for educational expansion.